Defining a weak lensing experiment in space - Cropper, M; Hoekstra, H; Kitching, T; Massey, R; Amiaux, J; Miller, L; Mellier, Y; Rhodes, J; Rowe, B; Pires, S; Saxton, C; Scaramella, R (2012)
This paper describes the definition of a typical next-generation space-based weak gravitational lensing experiment. We first adopt a set of top-level science requirements from the literature, based on the scale and depth of the galaxy sample, and the avoidance of systematic effects in the measurements which would bias the derived shear values. We then identify and categorise the contributing factors to the systematic effects, combining them with the correct weighting, in such a way as to fit within the top-level requirements. We present techniques which permit the performance to be evaluated and explore the limits at which the contributing factors can be managed. Besides the modelling biases resulting from the use of weighted moments, the main contributing factors are the reconstruction of the instrument point spread function (PSF), which is derived from the stellar images on the image, and the correction of the charge transfer inefficiency (CTI) in the CCD detectors caused by radiation damage.